Fraud Detection: Professional Skepticism and Quality Control System - Suhayati, Ely; Thufailah, Ashillah Arief (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2024)
AbstractFraud is defined as an intentional violation of the law which causes harm to others. This study aims to determine the influence of Professional Skepticism and Quality Control Systems on Fraud Detection. The method used is descriptive and verificative analysis with a quantitative approach to 40 auditors in 13 Bandung City Public Accounting Firms. Primary data was collected through survey method data collection techniques through questionnaires. The data analysis method uses multiple linear regression analysis, which tests using SPSS 23.0 software for Windows. The results of this study show that Professional Skepticism and Quality Control Systems affect Fraud Detection. This research contributes as an evaluative tool for auditors to increase professional skepticism by implementing a quality control system in their assignments. The novelty of thisresearch is that auditors require professional scepticism and good quality control systems to detect fraud quickly and accurately. Keywords:Professional Skepticism, Quality Control System, Fraud Detection